PENGARUH TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI - Gusnita, Yetri; Basri, Irfani; Ratna, Ellya (Universitas Negeri Padang, 2018)
This research is purpose to describe the influencing of using copy the master technic for writing explanation text ability for students class VIII SMP Negeri 15 Padang. The kind of this research is quantitative. The research uses experiment method which emphasizes on semu design experiment for one group pretest posttest design. There are three result on the research are (1) the students’ ability in writing explanation text before using copy the master technic at SMP Negeri 15 Padang is low and grades LdC with average 65,97, (2) the students’ ability in writing explanation text after using copy the master technic at SMP Negeri 15 Padang is high and grades BS with average 85,97, and (3) the significant influenced from using copy the master technic writing explanation text ability for students class VIII SMP Negeri 15 Padang. Based on t-test on the significant phase 95% and degrees of freedom (df) = nI because t-table<tcountt (1,70>10,91). Kata kunci: pengaruh, teknik copy the maser, menulis, teks eksplanasi